L'épave de Port Berteau II (Charente-Maritime) Un caboteur fluvio-maritime du haut Moyen Âge et son contexte nautique - Rieth, Éric (Documents d'archéologie française, 2001)
Discovered in 1973, the Port Berteau wreck lies at a depth of 7 metres in the Charente river below Samtes. Excavations (1992-1997) were carried out with the dual objective of studying both the hull's remains and its natural environment.Using the traditional techniques of ship archaeology to examine the wreck from the stem to the stern-post has enabled archaeologists to draw an 'architectural portrait" of an early 7th century coaster. The 14.30 metre carvel built "frame-first" boat was intended for river navigation and built to carry a cargo of up to ten tonnes. Using what could be called a naval archaeology approach, researchers have analysed the nver environment to reconstruct the natural landscape of the period. The Port Berteau II coaster thus provides a reference for carvel construction history in the Ponant, reviously attested only in 15th century texts.